POLA PENGASUHAN DEMOKRATIS ORANG TUA DAN GAYA KEPEMIMPINAN DEMOKRATIS GURU SEBAGAI PREDIKTOR KECERDASAN EMOSIONAL SISWA - Abdul Saman (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2010)
The objective of the study was to assess (1) descriptive about the students’ emotional intelligence, their perception towards democratic parenting model and the teacher’s democratic leadership style; (2) the correlation between the democratic parenting model with the emotional intelligence; (3) the teachers’ democratic leadership style with emotional intelligence, and 4) the correlation between the democratic parenting model and the teachers’ democratic leadership style with the emotional intelligence. The sample consisted of 182 student of SMA Negeri 2 Watampone, academic year 2007-2008, selected bay way of proporsional random sampling. The questionnaires to collect the data was designed to assess the perception about the democratic parenting by parents, the teachers’ democratic leadership style, and the emotional intelligence. The data were analyzed by employing the Simple Regression analysis technique for hypotesis one and two, and Multiple Regression for hypotesis three. The results of the correlation indicated (1) there was a significant correlation between emotional intelligence with the perception of democratic parenting model, (2) the emotional intelligence is significantly correlated with the perception obout the teacers’ democratic leadership style and (3) there was a significant correlation between the perception obout the democratic parenting model and the perception obout the teachers’ democratic leadership style with emotional intelligence. The two predictors provided an effective contribution at 46 percent against the variation of criteria emotional intelligence.